FENOMENA PSIKO-SOSIO LINGUISTIK DALAM PEMBELAJARAN BAHASA ARAB DI MUHAMMADIYAH BOARDING SCHOOL CEPU - Romadhon, Nur Naria Dina; Ramadhani, Gita Fitri; Langkau, Mifta Huljannah; Fikri, Shofil (STIQ Amuntai, 2024)
Psycho-socio-linguistics is a branch of linguistics that studies the relationship between language and the psychology and social aspects of language speakers. Psycho-socio-linguistics has an important role in the process of language learning, especially Arabic. Given the importance of the role of psycho-socio-linguistics, researchers want to study more deeply how psycho-socio-linguistic phenomena in Arabic language learning are carried out at Muhammadiyah Boarding School, Cepu. The purpose of this study is to deepen our understanding of how psychological and social aspects interact in the process of learning Arabic. The method used in this study is descriptive-qualitative. The data collection technique involves observing and interviewing. The results of this study reveal that psycho-socio-linguistics in Arabic language learning helps understand the role of psychological factors, such as language understanding and information processing, in the context of social and cultural interactions. The research also underscores the importance of understanding differences in dialects, grammar, and social contexts in Arabic language teaching. The results of this study can be used as a basis for the development of more effective learning strategies in Arabic language teaching by considering the psychological and social aspects involved.